2014
DOI: 10.1080/09168451.2014.877825
|View full text |Cite
|
Sign up to set email alerts
|

Insulin injection restored increased insulin receptor substrate (IRS)-2 protein during short-term protein restriction but did not affect reduced insulin-like growth factor (IGF)-I mRNA or increased triglyceride accumulation in the liver of rats

Abstract: Dietary protein restriction reduces insulin-like growth factor (IGF)-I synthesis and impairs growth. Moreover, insulin secretion is impaired and hepatic insulin signaling is activated presumably through upregulation of insulin receptor substrate (IRS)-2, which can stimulate lipogenesis thereby resulting in steatosis. In order to determine whether impaired insulin secretion is the primary cause of these changes, we injected insulin into protein-restricted rats and compensated for the reduction in insulin secret… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 38 publications
0
16
0
Order By: Relevance
“…We reported that protein deprivation increases IRS-2 protein levels in the liver; however it affects serine phosphorylation of IRS-1 in the muscle, which is shown to modulate insulin-dependent tyrosine phosphorylation of IRS-1 [6], indicating that each tissue possesses different mechanisms to modulate insulin signaling. We also found that the decrease in plasma insulin levels mediates that protein malnutrition increases IRS-2 protein levels in the liver [38]. Furthermore, amino acid deprivation may directly affect IRS-2 protein levels in cultured hepatocytes (manuscript in preparation).…”
Section: Effects Of Protein Malnutrition On Feeding-induced Phosphorymentioning
confidence: 66%
“…We reported that protein deprivation increases IRS-2 protein levels in the liver; however it affects serine phosphorylation of IRS-1 in the muscle, which is shown to modulate insulin-dependent tyrosine phosphorylation of IRS-1 [6], indicating that each tissue possesses different mechanisms to modulate insulin signaling. We also found that the decrease in plasma insulin levels mediates that protein malnutrition increases IRS-2 protein levels in the liver [38]. Furthermore, amino acid deprivation may directly affect IRS-2 protein levels in cultured hepatocytes (manuscript in preparation).…”
Section: Effects Of Protein Malnutrition On Feeding-induced Phosphorymentioning
confidence: 66%
“…Such a phenotype is typically observed in kwashiorkor, a form of severe protein malnutrition in infants and children. Detailed analysis in this animal model revealed that insulin sensitivity was enhanced in liver and muscle accompanied by a decrease in plasma insulin level (Toyoshima et al 2010, Ozaki et al 2014. In contrast, IGF1 signaling should be suppressed because growth was retarded in these animals.…”
Section: Cross-talk Of Igf Signals With Amino Acid Signalsmentioning
confidence: 91%
“…We have already reported that protein malnutrition enhances insulin signaling in rat liver followed by accumulation of hepatic lipid [6,7]. In addition, Aoyama et al have reported that triacylglycerol was accumulated in rat liver fed with low-arginine diet [5].…”
Section: Experimental Datamentioning
confidence: 94%
“…In the field of nutrition, we and other groups previously reported that dietary protein-malnutrition or protein-restriction caused growth retardation accompanied by hepatic triglyceride (TG) accumulation which was considered to be a kind of NAFLD [4][5][6][7]. It is well established that growth retardation is caused at least in part by the reduction of plasma insulin-like growth factor-I (IGF-I) level and actually it was reduced in animals fed a diet with protein-malnutrition or -restriction [4,8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation